2001
DOI: 10.1248/cpb.49.695
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Crinoidea. 2. Isolation and Structure of the Novel Type Gangliosides from the Feather Star Comanthus japonica.

Abstract: Two novel type gangliosides CJP2 and CJP3 have been obtained from the feather star Comanthus japonica. On the basis of methylation linkage analysis combined with ammonolysis and other chemical and spectroscopic evidence, the chemical structures of CJP2 and CJP3 were determined to be a a-9-O-Me-NeuGc-(2→3)-inositolphosphoceramide and a a-9-O-Me-NeuGc-(2→11)-a a-9-O-Me-NeuGc-(2→3)-inositolphosphoceramide, respectively. These gangliosides are unique in that they are inositolphosphoceramide derivatives possessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…NMR spectra were recorded on a Varian Unity-500 spectrometer ( Separation of CJP4 For the extraction and fractionation of the crude ganglioside fraction from the whole bodies of the feather star C. japonica (7.6 kg), the preceding paper should be referred to. 8 Fig. 2).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…NMR spectra were recorded on a Varian Unity-500 spectrometer ( Separation of CJP4 For the extraction and fractionation of the crude ganglioside fraction from the whole bodies of the feather star C. japonica (7.6 kg), the preceding paper should be referred to. 8 Fig. 2).…”
Section: Methodsmentioning
confidence: 98%
“…[1][2][3][4][5][6] In the study of the GSLs of the feather star Comanthus japonica (Nipponumishida in Japanese), we reported on the isolation and structural elucidation of inositolphosphoceramide, CJP1, 7) and the glycosyl inositolphosphoceramide-type gangliosides CJP2 and CJP3. 8) Continuing the preceding studies, further isolation and characterization of the more polar ganglioside from C. japonica was conducted. In this paper, we report on the isolation and structure of a glycosyl inositolphosphoceramide-type ganglioside from the whole bodies of C. japonica.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] In the study of the GSLs of the crinoidea, we reported on the isolation and structural elucidation of cerebrosides, 4) inositolphosphoceramide, 5) and the glycosyl inositolphosphoceramide-type gangliosides 6,7) from the feather star Comanthus japonica. Continuing the preceding studies, isolation and characterization of GSLs from the feather star Comanthina schlegeli (Hanaumishida in Japanese) was conducted.…”
mentioning
confidence: 99%